Partial diallel analysis of agronomic characters in rice (Oryza sativa L.) - Torres Toro, E.A.; Geraldi, IO (FapUNIFESP, 2007)
Rice (Oryza sativa L.) breeding seeking to combine high productivity and cold tolerance for the temperate Latin America region is an important challenge. We estimated some useful parameters which can be used to investigate the genetic control of agronomic characters in crosses combining cold tolerance and productivity. A partial diallel design was used in crosses between six tropical indica rice cold susceptible genotypes (group 1) and seven japonica or indica/japonica cold tolerant rice genotypes (group 2). Parents and crosses were evaluated for agronomic characters under field conditions in two different experiments in 2005. The results showed significant mid-parent heterosis for all characters (plant height, tiller number, days to 50% flowering, panicle length, grains per panicle, sterility, and one-hundred grain weight). The predominant direction of dominance effects was negative for days to 50% flowering, and positive for all the other characters. General combining ability (GCA) and specific combining ability (SCA) were significant for all characters, although the GCA effects of the two groups were more important than the SCA effects.